(untitled) (Research, Society and Development, 2022)
This study aims to estimate the prevalence of frailty in the elderly and analyze its association with sociodemographic factors, health conditions and social participation. It is a cross-sectional study with a quantitative, analytical approach, with 214 elderly people. Descriptive and inferential analysis was performed. The Clinical-Functional Vulnerability Index-20 was used for data collection and analyzed using descriptive statistics and 5% significance. Among the characteristics of the 214 elderly, 110 (51.4%) were classified as robust, 69 (32.2%) at risk of frailty and 35 (16.4%) frail, associated with more favorable and less favorable health conditions, respectively. . The study evidenced the prevalence of robust elderly, associated with socioeconomic factors and favorable health conditions, while the frail elderly in a situation of social vulnerability, demonstrating the importance of screening and consequent care for its prevention.